Impact of obesity on all-cause and cause-specific mortality among critically ill men and women: a cohort study on the eICU database - Li, Shan; Zhang, Wei; Fu, Zhiqing; Liu, Hongbin (Frontiers in Nutrition, 2023)
Background The effect of obesity on intensive care unit (ICU) outcomes among critically ill patients and whether there are sex differences have not been well investigated. We sought to determine the association between obesity and 30-day all-cause and cause-specific mortality among critically ill men and women. Methods Adult participants who had body mass index (BMI) measurements were included from the eICU database. Participants were divided into six groups according to BMI (kg/m2) categories (underweight, <18.5; normal weight, 18.5-24.9; overweight, 25-29.9; class I obesity, 30-34.9; class II obesity, 35-39.9; class III obesity, ≥40). A multivariable adjusted logistic model was conducted with odds ratios (ORs) and 95% confidence intervals (CIs). A cubic spline curve based on the generalized additive model was used to represent the nonlinear association. Stratified analysis and sensitivity analysis were also performed. Results A total of 160 940 individuals were included in the analysis. Compared with the class I obesity category, the underweight and normal weight categories had higher all-cause mortality, and the multivariable adjusted ORs were 1.62 (95% CI: 1.48-1.77) and 1.20 (95% CI: 1.13-1.27) for the general population, 1.76 (95% CI: 1.54-2.01) and 1.22 (95% CI: 1.13-1.32) for men, and 1.51 (95% CI: 1.33-1.71) and 1.16 (95% CI: 1.06-1.27) for women, respectively. Accordingly, multivariable adjusted ORs for the class III obesity category were 1.14 (95% CI: 1.05-1.24) for the general population, 1.18 (95% CI: 1.05-1.33) for men, and 1.10 (95% CI: 0.98-1.23) for women. With cubic spline curves, the association between BMI and all-cause mortality was U-shaped or J-shaped. Similar findings were observed for cause-specific mortality, with the underweight category associated with a higher risk of mortality. Class III obesity increased the risk of cardiovascular death among men (OR 1.51; 95% CI: 1.23-1.84) and increased the risk of other-cause death among women (OR 1.33; 95% CI: 1.10-1.61). Conclusion The obesity paradox appears to be suitable for all-cause and cause-specific mortality among critically ill men and women. However, the protective effect of obesity cannot be extended to severely obese individuals. The association between BMI and cardiovascular mortality was sex-specific and was more pronounced among men than among women.